Revise GCSE mathematics higher level - Hooper, Philip; Hunt, Sheila; Buzan, Tony (Hodder & Stoughton, 1997)
A practical, clear and lively guide to the essential facts needed for GCSE success. MindMaps, tips and practice questions motivate and guide the student throughout his or her revision.